Giant Dental Calculus Mimicking a Tumor: A Case Report - Parajuli , Asmita; Gurung, Gopal (Birat Journal of Health Sciences, 2023)
Dental calculus consists of mineralized bacterial plaque that forms on the surfaces of natural teeth and dental prostheses. Giant dental calculus mimicking a tumor is an unusual presentation. Buccal surfaces of the maxillary molars and the lingual surfaces of the mandibular anterior teeth are the most common location for calculus deposition. This case report presents a case of giant dental calculus mimicking a tumor on the labial surface of the mandible and its diagnostic dilemma, treatment and role of proper oral hygiene measures.